PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, DAN KEPEMILIKAN MANAJERIAL TERHADAP PRAKTIK PERATAAN LABA - Octavania, Meliza (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of the companyâs size, companyâs growth, and managerialownership to the income smoothing practice in the company which is listed in Indonesia Stock Exchange.Thesamples are 19 manfacturing companies which are listed in IDX during the years of 2010-2012. The samplingtechnique has been done by using purposive sampling method. The sample collection technique is documentation.The dependent variable in this research is the income smoothing while the independent variables in this researchare companyâs size, companyâs growth, and managerial ownership. The hypothesis test is conducted byperforming F test and t test with the significance level is 0.05. The result of Eckel index calculation shows that 8samples companies have done the income smoothing practice while the 11 companies are proven to conduct theincome smoothing practice. The result of simultaneous test by using F test shows that companyâs size,companyâs growth, and managerial ownership simultaneously have influence to the income smoothing practice.The result of partial test by using t test shows that the companyâs size variable has significant influence to theincome smoothing practice while the companyâs growth and managerial ownership have no significant influenceto the income smoothing practice.Keywords: companyâs size, companyâs growth, managerial ownership, income smoothing